Analysis of organoleptic, physical-chemical characteristics and concentrations of tartrazine yellow dye in tucupi samples sold at markets in Belém-PA (Research, Society and Development, 2023)
Cassava is a plant that belongs to the Euphorbiaceae family, subfamily Crotonoideae, tribe Manihota and genus Manihot. It has several derivatives among the best known: tucupi, a food widely consumed in the North region and has a yellow color, produced from roots of Manihot esculenta, and in this production of tucupi some food additives can be added that may or may not be toxic, such as the yellow dye tartrazine. Therefore, the present work aims to carry out physical-chemical and organoleptic analyzes and quantify the concentrations of the yellow tartrazine dye in tucupi samples sold at markets in Belém – PA. The research was carried out in three different fairs in the Belém region, that is, in three randomly selected kiosks, whose tucupi samples were packaged in plastic bottles. They were then sent to the bromatology laboratory to carry out organoleptic, physical chemical analyzes and quantification of the dye using the Ultraviolet/visible spectrophotometer, in which a scan was carried out of the five aqueous solutions containing tartrazine yellow dye: 2 mg /L, 5 mg/L, 7 mg/L, 10 mg/L and 15 mg/L, at a wavelength of 426 nm. The results obtained by the three samples in the physical-chemical and organoleptic tests are within the parameters of the Agricultural Defense Agency of the state of Pará, however in the spectrophotometric analyses, only one sample was approved while two samples have Tartrazine above that allowed by the national Agency health surveillance (ANVISA) of 7.5 mg/kg.